Aktivisme Dakwah Siber Di Tengah Konvergensi Media Digital - Jauhari, Minan (Institut Agama Islam Syarifuddin Lumajang, 2021)
This article discusses da'wah activism which is expressed in the midst of the convergence of digital media as a religious phenomenon. Da'wah activism is part of a religious activity that is an obligation for a Muslim, however, the display of da'wah messages expressed in the midst of the convergence of digital media does not only show it as a religious activity, but in appearance it also has the opportunity as a tool for political and ideological interests. In fact, Islam wants the da'wah to be carried out in the context of calling for goodness and preventing evil as the teachings of Islam. The method used in this study is to use a virtual ethnographic approach that focuses on artifacts, and digital traces related to da'wah messages displayed through cyber media. Furthermore, in order to understand religious phenomena that are expressed in the digital space, this study uses the concept of da'wah and cyber media as a choice of perspective, the aim is to be able to answer the question of how cyber da'wah activism is carried out by religious communities in the midst of digital media convergence. So it can be concluded that cyber da'wah activism, in addition to calling for good and preventing evil, turns out to be in its display of da'wah also depicts other interests such as political and ideological interests hidden behind da'wah messages displayed through digital media.Keywords : Da'wah Activism, Convergence, Digital Media